One-year and longer dual antiplatelet therapy after an acute coronary syndrome: a Belgian position paper: Endorsed by the Belgian Interdisciplinary Working Group of Acute Cardiology. Issue 1 (2nd January 2017) - Sinnaeve, Peter R.; Desmet, Walter; Descamps, Olivier; Gevaert, Sofie; De Backer, Guy; Kolh, Philippe; Vrolix, Mathias; Van De Borne, Philippe; De Meester, Antoine; Claeys, Marc J.; Beauloye, Christophe
Abstract: Acute coronary syndrome patients receive DAPT up to one year after their initial event. Exceptions to the guideline-recommended one-year rule, however, are not uncommon. The reasoning behind shorter treatments, such as unacceptable bleeding risk or urgent surgery, should be well documented in the patient's charts and discharge letter. Based on recent evidence, patients at high risk for repetitive events should continue on low-dose ticagrelor without a significant interruption at one year and indefinitely in the absence of excess bleeding risk. As there is currently no reimbursement, policy makers and insurers should be made aware of the continuing risk and unmet clinical need in this patient population. Nevertheless, many unsolved questions need to be answered, both through additional analyses from recent trials such as PEGASUS-TIMI 54 or DAPT, as well as new carefully designed clinical studies.